Building an ambidextrous organization: a maturity model for organizational ambidexterity - Katharina Stelzl; Maximilian Röglinger; Katrin Wyrtki (Business Research, 2020)
Organizational ambidexterity (OA) is an essential capability for organizations in turbulent environments, as it facilitates the simultaneous pursuit of exploitation and exploration. Over the last years, knowledge on OA has continuously matured, covering outcomes, moderators, and types of OA. However, little is known about how to build an ambidextrous organization in terms of what capabilities are needed and how they can be developed. To address this gap, we developed an organizational ambidexterity maturity model (OAMM) that assists organizations in becoming ambidextrous based on actionable practices (APs) structured according to five capability areas. In developing the OAMM, we conducted a structured literature review to compile APs and used card sorting to assign APs to maturity stages. We evaluated the OAMM based on literature-backed design objectives and discussions with practitioners. We also conducted an initial empirical validation of the APs' assignment to maturity stages. The OAMM extends the descriptive and prescriptive knowledge on OA by taking a holistic view on OA, by shedding light on the interrelation of different OA types, and by enabling the assessment of an organization's as-is and to-be OA maturity based on implemented APs.
Keywords: 650; Organizational ambidexterity; Exploitation; Exploration Maturity model; Capability development; Literature review; Cardsorting